PROPAGATION OF GUIDED HARMONIC WAVES IN ANISOTROPIC LAMINATES - Писаренко, Олександр (SWorldJournal, 2025)
In this study, a numerical method is presented to analyze the propagation characteristics of guided harmonic waves in multilayer anisotropic composite laminates. A generalized matrix of displacement and mechanical strain components for each local volume o